2019
DOI: 10.1039/c9en00055k
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between polystyrene nanoparticles and supported lipid bilayers: impact of charge and hydrophobicity modification by specific anions

Abstract: The interaction between nanoparticles and zwitterionic supported lipid bilayers is a multi-step process, with specific ions exerting their influences on electrostatic-driven NP deposition and hydrophobicity-induced membrane disruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…The Lau group at the University of Massachusetts Amherst has recently employed the SALB method to produce SLBs on gold surfaces in order to study nanoparticle−membrane interactions using surface-enhanced infrared absorption spectroscopy (SEIRAS). 114 The SEIRAS technique provides information about how nanoparticles interact with different components of the SLB platform, including hydrophobic and hydrophilic parts of the phospholipids along with interfacial water molecules on the SLB surface. Following this approach, it was determined that anionic carboxylic acid-functionalized polystyrene nanoparticles adsorb onto and penetrate into SLBs and cause changes in the interfacial water structure as well.…”
Section: ■ Application Examplesmentioning
confidence: 99%
“…The Lau group at the University of Massachusetts Amherst has recently employed the SALB method to produce SLBs on gold surfaces in order to study nanoparticle−membrane interactions using surface-enhanced infrared absorption spectroscopy (SEIRAS). 114 The SEIRAS technique provides information about how nanoparticles interact with different components of the SLB platform, including hydrophobic and hydrophilic parts of the phospholipids along with interfacial water molecules on the SLB surface. Following this approach, it was determined that anionic carboxylic acid-functionalized polystyrene nanoparticles adsorb onto and penetrate into SLBs and cause changes in the interfacial water structure as well.…”
Section: ■ Application Examplesmentioning
confidence: 99%
“…Extensive studies have shown that the physicochemical properties of the NP surface can effectively modulate the interaction of the NPs with cell membranes. For instance, in a recent work, we have shown that the grafting density of the ligands and the surface charge can significantly influence the insertion of NP into lipid bilayer or the adsorption of NP onto the surface of lipid bilayer . Additionally, the lateral organization of the hydrophobic and hydrophilic ligands on the surface of the NPs can also affect the interactions between NPs and lipid bilayers. For example, NP with a striped arrangement of ligands can more easily penetrate into the cell membrane than NP with randomly arranged ligands. , …”
Section: Introductionmentioning
confidence: 99%
“…Following bilayer formation, 150 mM NaCl buffered with 5 mM HEPES at pH 7.4 was pumped for 10 min, and the NP sample was pumped for 1 h onto the SLBs at 100 ppm in the same saline buffer. For quantification, the seventh harmonic was chosen for maximum data robustness. , When the adsorbed PS NPs formed a homogeneous film and the dissipative energy losses were small (Δ D /Δ F < 1 × 10 –7 Hz –1 for all overtones, normalized Δ F equal for each overtone), the Sauerbrey equation was used to calculate the deposited mass Δm from the frequency variations: normalΔ m = prefix− normalΔ F n n c where Δ F n is the measured frequency shift at overtone number n and C is the mass sensitivity constant that equals 17.7 ng/Hz cm 2 . Measurements were conducted in triplicate and reported as the mean ± standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, cell culture experiments show that cellular binding of NPs disrupts the membrane potential, not only altering the normal cell cycle progression but also inducing malignant transformations and avoiding tissue regeneration . In vitro techniques taking advantage of the fact that PS NPs can be adsorbed on model membranes have stimulated intense research providing molecular details not visible at the cellular level. Thus, the alteration of ionic gradients around cells by PS NPs has been linked to a variety of molecular mechanisms such as NP internalization, local collapse of membrane integrity, creation of hydrophilic pores, or even the physical blockage of ion channels such as K + or Na + ones .…”
Section: Introductionmentioning
confidence: 99%